Simple gene transfer technique based on I-SceI meganuclease and cytoplasmic injection in IVF bovine embryos - Bevacqua, Romina Jimena (2013)
Although transgenic methods in mammals are inefficient, an easy and highly efficient transgenesis systemusing I-SceI meganuclease (intron-encoded endonuclease fromS. cerevisiae)was recently described in Xenopus. The method consisted of injection into fertilized eggs of an I-SceI reaction mixture with a plasmid DNA carrying the transgene, flanked by the meganuclease recognition sites (pIS). In the present study, the effects of I-SceI on gene transfer were tested apparently for the first time in mammals, in particular, in cattle. Various conditions were evaluated, including three concentrations of the plasmid pIS Pax6egfp, carrying I-SceI recognition sites flanking egfp under Pax6 promoter and two injection times (before IVM and after IVF) of pIS CAGegfp, carrying I-SceI sites fanking egfp under CAG promoter. In addition, the quantity of transgenewasmeasured using quantitative polymerase chain reaction, and presence of transgene signals was evaluated using fluorescence in situ hybridization analysis. Transgene expression rateswere higher (P< 0.05) for groups treated after IVF (79.1%, 91/115 and 63.0%, 75/ 119) than before IVM (32.6%, 31/95 and 34.7%, 33/95), with and without I-SceI, respectively. Interestingly, injectionwith pIS plus I-SceI after IVF increased frequency (P<0.05) of nonmosaic transgene-expressing embryos (58.3%, 42/72 vs. 29.7%, 25/84) for pIS plus I-SceI and pIS alone. Based on fluorescence in situ hybridization analysis, injectionwith I-SceI increased (P<0.05) the proportion of embryos with transgene signals in all blastomeres compared with pIS alone (44.0%,11/25 vs. 6.9%, 2/29) for pIS plus I-SceI and pIS alone. In addition, transgene copy number was numerically higher for the group treated with pIS plus I-SceI compared with pIS alone. In conclusion, I-SceI gene transfer increased transgene signals in bovine embryos.